Multi-axial Fatigue of Trabecular Bone with Respect to Normal Walking - Mostakhdemin, Mohammad; Sadegh Amiri, Iraj.; Syahrom, Ardiyansyah; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book focuses on the analysis and treatment of osteoporotic bone based on drug administration, tracking fatigue behavior and taking into consideration the mechanical interaction of implants with trabecular bone. Weak trabeculae are one of the most important clinical features that need to be addressed in order to prevent hip joint fractures.
Introduction of Bone Study -- Literature Review Fatigue Analysis in Trabecular Bone -- Methodology of Fatigue Life Simulation in Trabecular Bone -- Result and Discussion of Static and Dynamic Analysis of Trabecular Bone -- Conclusion and Recommendation of Multi-Axial Fatigue of Trabecular Bone in Normal Walking.
Keywords: Engineering; Orthopedics; Rehabilitation; Bioinformatics; Computational intelligence; Structural mechanics; Biomedical engineering; Engineering; Biomedical Engineering; Orthopedics; Structural Mechanics; Computational Intelligence; Rehabilitation; Computational Biology/Bioinformatics.; Electronic books